Analysis of mind - Russell, Bertrand , 1872-1970.; Buzurgmihr, Manuchihr; Russell, Bertrand, 1872-1970; Franklin Book Program Collection (Library of Congress) (London : George Allen & Unwin Ltd., 1921)
This book has grown out of an attempt to harmonize two different ten dencies, one in psychology, the other in physics, with both of which I find myself in sympathy, although at first sight they might seem incons istent. On the one hand, many psychologists, especially those of the be haviourist school, tend to adopt what is essentially a materialistic po sition, as a matter of method if not of metaphysics.
Library of Congress. Franklin Book Program Collection, no. P671.
Includes bibliographical references.
In Persian; translated from English.
Keywords: Psychology